# What is x squared minus 3x minus 40?

Would you like to merge this question into it?

#### already exists as an alternate of this question.

Would you like to make it the primary and merge this question into it?

#### exists and is an alternate of .

In Algebra
It is: (x+5)(x-8) when factored
1 person found this useful

# What is the domain of 3x plus 1 over x squared minus 2x?

For this question, the domain can be anything, as long as the denominator is not 0. If your question was (3x+1)/(x 2 -2x), the domain is all real numbers except for 0, 2. If your question was [(3x+1)/x 2 ] - 2x, then x is not equal to zero.

# Solve x squared plus 3x minus 1 by completing the square?

xÂ² + 3x - 1 = [ xÂ² + 3x + (3/2)Â²] - 1 - (3/2)Â² = (x + 3/2)Â² - 1 - (9/4) = (x + 3/2)Â² - (13/4) if you are still confused, i want you to follow the related link that explains the concept of completing the square clearly.

# What is the shape of the curve y equals 3x squared plus x minus 2?

A parabola You can find the peak of this parabola by taking it's derivative and finding the point where it's slope is equal to zero: y = 3x 2 + x - 2 y' = 6x + 1 Let y' = 0 0 = 6x + 1 x = -1/6 Now find the y co-ordinate: y = 3(-1/6) 2 + (-1/6) - 2 y = 3/18 - 1/6 - 2 y = -2 So this parabola's vertex will be located at the point (-1/6, -2).

# 3x squared minus x minus 2?

What is the question? Do you want to factor 3x 2 -x -2?. If that is the question the answer is (3x + 2)(x-1)

# X squared minus 49?

(x-7)(x+7) but what if the question was x squared PLUS 49 x^2 + 49 help

# How do you solve x squared minus 3x 10?

X squared - 3x - 10 = 0. (x-5) (x+2) = 0. x - 5 = 0. x + 2 = 0. X= 5 x = -2

# Factor x cubed plus x squared minus 3x minus 3?

xÂ³ + xÂ² - 3x - 3 = (x + 1)(x + â3) (x - â3).

# What is 3x squared minus x squared?

3x^2 - x^2 = (3 - 1)(x^2) = 2x^2\nIt is a good idea early one in math to think of things like this..\n. \njust like we can add or subtract numbers, we can add or subtracts x^2 or x^3 or squareroots of x...\n. \nSo think of 3x^2 as three (x^2)s...that is to say x^2 is something, like apples or oranges and you are just taking 3 or them and taking away one of them, so you have 2 of them.

# What is 6x squared minus x?

6x 2 - x. You don't have enough information to take this any further or solve it

# How would you solve x squared minus 3x minus 15 equals 0?

3x 2 when x = 2 . is the answer 3 X 4 = 12 . or is the answer (3 X 2) 2 = 6 2 = 36

# 3x squared minus 2x when x equals 5?

You fill in for x and solve the equation 3(5)^2 - 2(5) 15^2 - 10; now solve

# Sketch f of x equals 3x minus 3x?

Let's simplify: f(x) = 3x-3x, so f(x) =0, so y=0 The graph is a line along the x-axis.

# How do you solve 3x square minus x minus102 equals 0?

3x 2 - x - 102 = 0 Factor the left side: (3x + 17) times (x - 6) = 0 The two solutions are: 3x + 17 = 0 3x = -17 x = -17/3 and x - 6 = 0 x = 6

# X squared plus 3x minus 6?

X 2 +3x-6=0 A=1 B=3 C=-6 D=B 2 -4AC=3 2 -4*1*-6=33 X1= (-B+âD)/(2A)=(-3+â33)/(2*6)=1,372281323 X2= (-B-âD)/(2A)=(-3-â33)/(2*6)=-4,372281323

# Can you factor 3x squared minus 3x -4?

Yes, but not in rational terms. The factorisation is: {x - [3-sqrt(57)]/6} * {x - [3+sqrt(57)]/6}

# How do you complete the square of 3x squared minus 2x minus 5 equals 0?

Let f = 3x 2 - 2x - 5 = 0. Let's also jolly this up, with a few more letters: Let, also, g = 3f and z = 3x. Then, g = 9x 2 - 6x - 15 = z 2 - 2z - 15 = (z 2 - 2z + 1) - 16. (This completes the square.) Now, also let w = z - 1 = 3x - 1. Then, g = w 2 - 16, which easily factorises, as g = (w - 4)(w + 4) = (3x - 1 - 4)(3x - 1 + 4); = (3x - 5)(3x + 3); and, since g = 3f, f = â(3x - 5)(3x + 3) = (3x - 5)(x + 1), thus giving the correct factors of f = 3x 2 - 2x - 5. The solution follows from this: f = 0, exactly when either of the two factors given above is zero; that is, when x = 1â or x = -1. Completing the square, as you can see, is not always the easiest way to obtain factors; but it has the advantage of working, in every case.

# How do you factor 3x cubed x squared minus 25?

well, i believe it goes like this (not certain) 25 is the only not prime number so... 3xcubed x squared -5 squared

# How do you factor 3x squared minus 588?

3xx-588 3(xx-196) Factor (long): xx+0x-196 axx+bx+c a=1 b=0 c=-196 Multiply a and c: 1*-196=-196 Find multiples of ac that add up to b (d,e [ie de=ac, d+e=b]): -196=-1*2*2*7*7, -2*98, 2*-98 -7*28, 7*-28 -4*49, 4*-49 -14*14, Rewrite axx+bx+c into axx+dx+ex+c: 3(xx-14x+14x-196) Factor sets of terms (ie axx+dx, and ex+c): 3(xx-14x+14x-196) 3(x(x-14)+14(x-14)) Combine like terms: 3(x(x-14)+14(x-14)) 3(x-14)(x+14) Factor (short): 3(xx+0x-196) Factors of -196, find which ones add up to 0 -196=-1*2*2*7*7, -2*98, 2*-98 -7*28, 7*-28 -4*49, 4*-49 - 14*14, Rewrite in form of (x+d)(x+e) 3(x+14)(x-14) Factor (shorter): -when a polynomial takes the form of xx-c, it can be factored into the form: (x+sqrt(c))(x-sqrt(c)) sqrt(196)=14,-14 3(x+14)(x-14)

# What is x squared minus 3x minus 28 for x?

This expression doesn't tell what 'x' has to be. In fact, 'x' can be anything. Your choice. Every time you change 'x', the expression becomes a different number. If this expression were equal to something, then we could get some exercise figuring out what 'x' must be in order to make the equation true. But in its present form, it doesn't say anything, so there's nothing to be proven true or false. It's just a number that depends on what 'x' is.

# What is x if 2x squared plus 3x minus 5 equals 0?

2x 2 + 3x - 5 = 0 2x 2 - 2x + 5x - 5 = 0 2x(x - 1) + 5(x - 1) = 0 (x - 1)(2x + 5) = 0 x - 1 = 0 or 2x + 5 = 0 x = 1 or x = -5/2

# How do you factor 3x squared minus 5x minus 12?

Your factors must begin 3x and x to give 3x 2 . The factors of 12 are 1/12, 2/6 and 3/4. Which pair, together with 3x and x, can add to -5? 3 and 4 seem to fit the bill: (3x + 4)(x - 3)

# X squared minus x?

x 2 - x = 0 ? . simplifying to the initial equation by grouping of terms: . x(x-1) = 0 . is true when x = 1 or x = 0 by the quadratic formula we can find the root (solution) of the equation as follows: the equation can be rewritten as (1(x 2 )) - (1(x)) + 0 = 0 . so that we can see the form a x 2 + b x + c = 0 Substituting our values for a , b and c into the formula, we get x = (- b Â± â( b 2 - 4 ac )) Ã· 2 a . x = (-(-1) Â± â(-1 2 - 4x1x0)) Ã· (2 x 1) . x = (-(-1) Â± â(1 - 0)) Ã· 2 . x = (1 Â± 1) Ã· 2 . x = 2 Ã· 2 = 1 . OR x = 0 Ã· 2 = 0 . i.e. the roots (solution) of the equation x 2 - x = 0 ? are when x = 1 or x = 0

# How would you factor 3x squared plus x minus 10?

3x**2+x-10 Multiply first and last terms 3*-10=-30 Find factors of -30 that add up to second term 6+-5=1 rewrite 3x**2-5x+6x-10 Factor pairs of terms 3x**2-5x+6x-10 = x(3x-5)+2(3x-5) Factor x(3x-5)+2(x-5) = (x+2)(3x-5)

# What is the factor of 3x squared minus 4x minus 5?

3x 2 - 4x - 5 does not have rational factors. Its roots are x = [4 +/- sqrt(76)]/6 ie -0.7863 and 2.11963 (approx). So the factors are (x + 0.7863) and (x - 2.11963)

# Where are the points of intersection on the curves y equals 5x squared minus 2x plus 1 and y equals 6 minus 3x minus x squared?

So by definition both equations equal one another: 5x 2 -2x+1 = 6-3x-x 2 5x 2 +x 2 -2x+3x+1-6 = 0 6x 2 +x-5 = 0 Factor the above equation with the help of the quadratic equation formula: (6x-5)(x+1) = 0 When x = -1 y = 8 When x = 5/6 y = 101/36 Therefore the curves intersect at points: (-1, 8) and (5/6, 101/36)

# How do you solve x squared plus 3x minus 15 equals 0?

x 2 + 3x - 15 = 0 you need to use the quadratic equation... since you have x to the second degree you will get two answers... yours two answers are... x = 2.6533 and -5.6533

# What is x squared minus 100?

That's going to depend on the value of 'x'. But no matter what 'x' is, (x 2 -100) will be equal to the product of (ten more than 'x') and (ten less than 'x').

# What is x squared minus10 over x squared minus 4 plus 3x over x squared minus 4?

For any x â  0, x 2 -10/x 2 - 4 +3x/x 2 - 4 LCD = x 2 , multiply each term by their missing element of LCD = (x 4 + 10 +3x - 8x 2 )/x = (x 4 - 8x 2 + 3x + 10)/x 2

# What is the solution to x cubed minus 3x squared plus 6x plus 5 divided by x minus 2?

(x 3 -3x 2 +6x+5)/(x-2) = x 2 -x+4 remainder 13 or as x 2 -x+4+13/(x-2) It's difficult to show the workings out on this computer but division in algebra has a lot in common when doing long division with integers.

# How do you solve x squared minus 3x plus 2 equals 0?

you can factor x^2-3x+2=0 (x-2)(x-1)=0 x=1 x=2 you can use the quadratic formula ax^2+bx+c=0 x^2-3x+2=0 a=1 b= -3 c=2

# How many x-intercepts does 3x squared minus 5x minus 1 equals y have?

It has two because (b^2-4ac) is positive, 37. a=3 b=-5 c=-1 If it was zero then it would be one intercept. If negative there would be none. This is called the determinant.

# What is x cubed plus 3x squared minus 22x minus 90 divided by x minus 5 giving a reason why your answer is correct?

x 3 +3x 2 -22x-90 divided by x-5 equals x 2 +8x+18 For the answer to be correct then the quotient multiplied by the divisor must be equal to the dividend. Hence:- (x-5)*(x 2 +8x+18) Multiplying out the brackets term by term: x 3 -5x 2 +8x 2 -40x+18x-90 Collecting like terms in descending order: x 3 +3x 2 -22x-90 So the answer is correct.

# How do you factor 3x squared minus 3x minus 60?

3x 2 - 3x - 60 = 3(x 2 - x - 20) = 3(x 2 - 5x + 4x - 20) = 3(x[x - 5] + 4[x - 5]) = 3(x + 4)(x - 5)

# What is the answer to x squared minus eighteen?

That completely depends on what 'x' is at the moment, and as soon as 'x' changes, (x 2 - 18) also changes immediately.

# How do you factor 3x squared minus 3x minus 6?

3x 2 - 3x - 6 = 3(x 2 - x - 2) = 3 (x + 1) (x - 2)

# What is x squared minus nine?

It factors into (x-3)(x+3) as it follows the difference of squares rule. However, since you gave me an expression and not an equation, I cannot solve this expression beyond this point. If x^2-9=0. Then you can see that (x-3)=0 and (x+3)=0. Thus x=-3, 3.

# What is 2x squared minus x?

The equation: 2x 2 - x Plug in a number: like 10. 2 * 10 2 - 10 = 2 * 100 - 10 = 200 - 10 = 190 In this case x would equal ten.

# How do you factor 2x squared plus 3x equals 3x minus 1 squared minus x squared?

If you mean 2x 2 + 3x = (3x - 1) 2 - x 2 Then you can solve it this way: Expand: 2x 2 + 3x = 9x 2 - 6x + 1 - x 2 Group like terms: 2x 2 + 3x = 8x 2 - 6x + 1 6x 2 - 9x - 1 = 0 Complete the square: 6x 2 - 9x = 1 x 2 - 3x/2 = 1/6 x 2 - 3x/2 + 9/16 = 1/6 + 9/16 (x - 3/4) 2 = 8/48 + 27/48 (x - 3/4) 2 = 35/48 Solve for x: x - 3/4 = Â± â(35/48) x - 3/4 = Â± â(35/3) / 4 x = 3/4 Â± â(35/3) / 4 x = [3 Â± â(35/3)] / 4 If you mean something else, then you'll need to be clearer with your question.

# How do you find the solution for 3x squared minus x plus 5 equals zero?

The answer will wind up being a pair of complex numbers. One way you can solve for x is by completing the square: 3x 2 - x + 5 = 0 3x 2 - x = -5 x 2 - x/3 = -5/3 x 2 - x/3 + 1/36 = -5/3 + 1/36 (x - 1/6) 2 = (-60 + 1) / 36 (x - 1/6) 2 = -59 / 36 x - 1/6 = Â± â(-59 / 36) x - 1/6 = Â± iâ(59 / 36) x - 1/6 = Â± iâ59 / 6 x = 1/6 Â± iâ59 / 6 x = (1 Â± iâ59) / 6

# How do you factoring by grouping in 6x cubed plus 9 x squared minus 2x squared minus 3x?

6x 3 + 9x 2 - 2x 2 - 3x Before any grouping, take out the common factor, x, to give x*(6x 2 + 9x - 2x - 3) = x*[3x*(2x + 3) - 1*(2x + 3)] = x*(2x + 3)*(3x - 1)

# How do you solve 3x squared plus x minus 14?

Do you mean: 3x 2 +x-14 = 0 If so the solutions are: x = 2 and x = -7/3 using the quadratic equation formula

# What is the solution to 2x squared minus 3x squared plus 5x minus 4 when x equals negative 1?

This is not calculus. Please post this in the correct forum. However, 2x2 - 3x2 +5x - 4 = -1 therefore -x2+4x-3 = 0 therefore x2-4x+3 = 0 therefore (x-3)(x-1)=0 therefore x = 3 or x = 1. Put your questions in the correct category. Makes then more likely to be answered correctly.

# What is x squared minus 6x?

Since the exponents are not the same, 6x cannot be subtracted from x squared unless we know what the value of x is, so you would just leave it as is.

# How would you factor x squared plus 3x minus 10?

X 2 + 3x - 10 What two factors of - 10 add up to 3 ? (x + 5)(x - 2) ===

# What is 3x equals x squared minus 2x?

3X = x 2 - 2x subtract 3X from each side X 2 - 5X = 0 factor out an X X(X - 5) = 0 = X = 0 --------or X = 5 --------

# What is the solution set of the equation x squared minus 3x minus 4 equals 0?

X2 - 3X - 4 = 0 factored (X + 1)(X - 4) ---------------- X = - 1 X = 4 ------------------- (- 1, 0) and (4, 0) ==solution set of X interception points

# How do you factor 3x squared minus 12?

3X 2 - 12 3(X 2 - 4) =All the factoring that can be done here.

# What are the factors of 3x squared minus x plus 4?

That doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (1 plus or minus the square root of -47) divided by 6. x = 0.16666 + 1.142609100066840 i = 1 st root = r 1 x = 0.16666 - 1.142609100066840 i = 2 nd root = r 2 where i is the square root of negative one. Then factor as (x - r 1 )(x - r 2 ) Or you can complete the square to transform the trinomial into the difference of the squares 3x 2 - x + 4 factor out 3 = 3(x 2 -(1/3)x + 4/3) add and subtract (1/6) 2 = 3[x 2 -(1/3)x + (1/6) 2 - 1/36 + 4/3] simplify = 3[(x - 1/6) 2 + 47/36] write 47/36 = - (-47/36) = - (â-1â47/6) 2 = - (iâ47/6) 2 = 3[(x - 1/6) 2 - (iâ47/6) 2 ] write the difference of the squares = 3[(x - 1/6) - (iâ47/6)][(x - 1/6) + (iâ47/6)] = 3[(x - (1 + iâ47)/6)][(x - (1 - iâ47)/6].

# What is the x-intercept of negative 3x squared plus 24x minus 19?

The idea is to solve the equation -3x 2 + 24x - 19 = 0.You can use the quadratic formula for this, using a = -3, b = 24, c= 19. Or complete the square since dividing by -3 will give us 8x, aneven coefficient. -3x 2 + 24x - 19 = 0 (add and subtract 48 to the leftside) -3x 2 + 24x -48 + 29 = 0 (subtract 29 to both sides, andfactor out -3) -3(x 2 - 8x + 16) = -29 (divide by -3 to both sides) (x - 4) 2 = 29/3 x - 4 = Â± â(29/3) (add 4 to both sides) x = 4 Â± â(29/3) (multiply by 3/3 inside the radical, if you want torationalize the denominator) x = 4 Â± (â87)/3

# What is x squared minus 4x?

The value of that expression depends on the value of "x". You can't really simplify it, except that you can factor it by separating the common factor "x".